N-linoleyltyrosine ameliorates high-fat diet-induced obesity in C57BL/6 mice via cannabinoid receptor regulation - Yang, Zheng-yu; Wu, Yi-ying; Zhou, Yi; Yang, Yun-qi; Zhang, Jia-hui; He, Tao; Liu, Sha (Frontiers in Endocrinology, 2022)
N-linoleyltyrosine (NITyr) showed benign effects in preclinical studies. The research discussed the effect of NITyr on a high-fat diet (HFD) induced obese (DIO) mice. The DIO mice were established by feeding an HFD for 12 weeks and subsequently administrated orally with NITyr (30, 60 and 100 mg/kg) for four weeks. The samples of serum, liver, adipose and brain were prepared for detection. NITyr at 60 and 100 mg/kg/day suppressed the weight gain without affecting on water and food intake. Accordingly, NITyr reduced the weight of adipose and the area of individual adipocytes, and increased the number of adipocytes. Moreover, NITyr didn’t affect the appetite related indexes such as ghrelin, peptide YY and brain-derived neurotrophic factor. Besides, NITyr didn’t affect other organ coefficients except for the liver. Correspondingly, NITyr reduced alanine aminotransferase and aspartate aminotransferase levels, yet didn’t influence IL-1β and TNF-α levels, and the pathological injury of the liver. Levels of Triacylglycerol (TG), total cholesterol (TC), glucose, insulin, adiponectin and leptin in serum were assessed to evaluate the effect of NITyr on glucose and lipid metabolism. NITyr decreased the levels of TG, TC and glucose, and didn’t affect insulin, adiponectin and leptin levels. Meanwhile, NITyr up-regulated the cannabinoid receptor 2 (CB2) expressions and down-regulated cannabinoid receptor 1 (CB1) expressions. Overall, NITyr suppressed lipid accumulation via improving lipid and glucose metabolism involving CB1 and CB2 receptor.